Calculation of the Operational Risk of a Non–Financial Company Using the Concept of VaR - Kostenarov, Krasimir (Economy and Business Yearbook, 2022)
VaR is a relatively wellknown concept for calculating the risk when it comes to managing financial instruments. Financial instruments are characterized by the availability of easily accessible and qualitative statistical information, which leads to the relatively easy calculation of both VaR and other risk indicators. Making a quantitative assessment of the risk of a non-financial company has difficulties in this context. The main difficulty is to find a quantitative assessment of the different business processes in the company. The purpose of this article is to present a methodology for calculating risk, which uses the principles and methods laid down in the calculation of VaR, but applied to the operational risk of a non-financial company.